2018
DOI: 10.14720/aas.2018.111.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical changes in Matricaria chamomilla induced by Pseudomonas fluorescens and water deficit stress

Abstract: Environmental stresses and rhizosphere microorganisms affect growth parameters and accumulation of active ingredients especially in plants with medicinal properties. The present study examined the effects of chamomile (Matricaria chamomilla L.) seedling inoculation with Pseudomonas fluorescens PF-135 strain on its growth parameters, photosynthetic pigments, proline, malondialdehyde (MDA), and hydrogen peroxide (H 2 O 2 ) content, and essential oil concentration at both regular watering and water deficit experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Drought stress induces accumulation of ROS such as superoxide radicals and H 2 O 2 which cause lipid peroxidation of cellular membranes and protein denaturation, and consequently leads to cell death (Masoudi-Sadaghiani et al, 2011;Mohammadi et al, 2018 (Fahad et al, 2017). The enzymatic antioxidants are known to be the most potential antioxidant in scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought stress induces accumulation of ROS such as superoxide radicals and H 2 O 2 which cause lipid peroxidation of cellular membranes and protein denaturation, and consequently leads to cell death (Masoudi-Sadaghiani et al, 2011;Mohammadi et al, 2018 (Fahad et al, 2017). The enzymatic antioxidants are known to be the most potential antioxidant in scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to drought leads to an increase in the accumulation of proline and total soluble sugar (TSS) that helps to maintain the plant water potential, membrane integrity, and stabilization of subcellular structures (Mohammadi et al, 2018). An increase in proline and TSS was observed in the uninoculated plants exposed to drought, probably due to osmotic adjustment (Figure 4A and B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1D,E). Under stressful conditions, changes in Pro and SS levels in plants indicate an adjustment or a self‐protection mechanism to prevent protein denaturation and induce stress tolerance (Mohammadi et al 2018). In accordance with our findings, Zhou et al (2011) also demonstrated that an increase of W and N doses had a reversal effect on the accumulation of Pro and SS contents in Malcolmia africana and Bassia hyssopifolia under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the growing conditions during the period of April to May were more favourable for the peat treatment in comparison to the other substrate treatments, probably due to the better water retention properties and the alleviation of high-temperature-induced stress conditions for plants. Similarly, Baghbani-Arani et al 25 and Mohammadi et al 26 reported that water stress affects the growth of medicinal plants such as fenugreek (Trigonella foenum-graecum L.) and chamomile (Matricaria chamomilla L.).…”
Section: Plant Growthmentioning
confidence: 99%